Unified numerical model of wind-induced response of long-span structures: Aerostatic torsional divergence, flutter, and random buffeting. (November 2022) - Wang, Shi-jun; Zhang, Wen-ming; Tian, Yun-fei; Bao, Cheng-jia; Chen, Zi-yun
Abstract: Wind-induced vibrations of super-long span bridges are known to be coupled, which fact is neglected in conventional calculations. In this paper, this coupling issue is tackled by a quasi-steady approach. A unified model of aerodynamic forces acting on the bridge structure is proposed. The aerostatic coefficients, transient incidence angle, fluctuating wind velocity, relative displacement and velocity of the bridge structure are used to represent the aerodynamic force acting on the deck, which allows one to avoid its conventional breakdown into random buffeting force, self-excited aerodynamic force, and aerostatic force. The proposed method is implemented in the developed software program to achieve the full process analysis of dynamic hazards, including aerostatic torsional divergence, random buffeting, and flutter divergence. Criteria for various types of hazards are then established. The feasibility and effectiveness of the proposed method and computation program are verified using the engineering examples of available long-span bridges. The results obtained show that the turbulence flow reduces the critical wind speed of torsional divergence of the structure, and changes the form of instability. Aerodynamic damping has a delay effect on this dynamic instability. Turbulent flow, aerodynamic admittance, and geometric nonlinearity are shown to have a significant impact on the flutter process. Finally, in the case of buffeting, it is proved that disregard of high-order terms of the aerodynamic force may lead to non-conservative estimations.